Efficiency of the use of Asphalt Concrete Pavement in Road Construction (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article is dedicated to analyzing the effectiveness of using asphalt concrete coatings in road construction. The study examines road quality, economic efficiency, and environmental impacts. The durability and service life of asphalt concrete coatings, as well as the advantages of construction costs and technologies, are highlighted.